Assessing the impact of emotional intelligence on employee customer service delivery: A case study of banking sector in Ghana - Kportufe, Joyce (2015)
A thesis submitted to the Department of Social Sciences of the Kwame Nkrumah University of Science and Technology in partial fulfillment of the award of the degree of Master of Business Administration (Human Resources Management).